# Long Questions

Find the equation of any one straight line passing through the point (4, -1) and making an angle of 45° with the line 2x - 3y = 5.

The required straight line pass through the point (4, -1), so, we have, (y - y

_{1}) = m

_{1}(x - x

_{1}) or, y + 1 = m

_{1}(x - 4) --- (i)

Also, the required line makes an angle of θ = 45° with the line 2x - 3y = 5 whose slope,

m_{2} = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = $\frac{2}{3}$.

So, the angles between these lines is given by,
tanθ = ±$\frac{m_1\text{ - }m_2}{1 \text{ + }m_1 m_2}$
or, tan45° = ±$\frac{m_1\text{ - }\frac{2}{3}}{1 \text{ + }m_1 \frac{2}{3}}$

or, 1 = ±$\frac{3m_1\text{ - 2}}{3 \text{ + }2m_1}$

or, 1
= ±$\frac{3m_1\text{ - 2}}{3 \text{ + }2m_1}$

or, 3 + 2m_{1} = ±3m_{1} - 2

Taking positive sign,

3 + 2m_{1} = 3m_{1} - 2

so, m_{1} = 5

Using its value at (i),

y + 1 = 5(x - 4)

so, 5x - y - 21 = 0 --- (A)

Taking negative sign,

3 + 2m_{1} = -(3m_{1} - 2)

or, 5m_{1} = -1

so, m_{1} = -$\frac{1}{5}$

Using its value at (i),

y + 1 = -$\frac{1}{5}$(x - 4)

or, 5y + 5 = -x + 4

so, x + 5y + 1 = 0 --- (B)

Hence, from (A) and (B), 5x - y - 21 = 0 and x + 5y + 1 = 0 are required equations.

If the acute angle between the pair of straight lines represented by x^{2}
- 2xycosecθ + y^{2} = 0 is α, then prove that: α = 90° - θ.

Given equation: x

^{2}- 2xycosecθ + y

^{2}= 0 --- (i)

Comparing it with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 1, h = -cosecθ, b = 1

Now, α be the acute angle between lines represented by equation (i), we have,
tanα = +$\frac{2\sqrt{h^2\text{ - ab}}}{\text{a + b}}$
or, tanα = +$\frac{2\sqrt{(-cosec^2\theta) \text{ - 1}}}{\text{1 + 1}}$

or, tanα = $\sqrt{cosec^2\theta \text{ - 1}}$

or, tanα = $\sqrt{cot^2\theta}$

or, tanα = cotθ

or, tanα = tan(90° - θ)

so, α = 90° - θ

Hence, it is proved that the acute angle between a pair of lines represented by the given equation is 90° - θ.

**Note:**Acute angle is an angle less than 90°. So, we take only positive sign. If there was obtuse angle in the question then we would take negative sign.

Find the angles between the lines represented by the equation x^{2} +
4xy + y^{2} = 0.

Given equation: x

^{2}+ 4xy + y

^{2}= 0 --- (i)

Comparing it with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 1, h = 2, b = 1

Let, θ be the angle between lines represented by equation (i), we know,
tanθ = $\frac{\pm 2\sqrt{h^2\text{ - ab}}}{\text{a + b}}$
or, tanθ = $\frac{\pm 2\sqrt{2^2\text{ - 1}}}{2}$

or, tanθ = ±$\sqrt3$

Taking positive,

or, tanθ = tan60°

so, θ = 60°

Taking negative,

or, tanθ = -tan60°

or, tanθ = tan(180° - 60°)

so, θ = 120°

Hence, the angle between a pair of lines represented by the given equation is 60° or 120°.

Find the separate equations of the pair of lines represented by the equation
6x^{2} - xy - y^{2} = 0. Also find the angle between them.

Given equation: 6x^{2} - xy - y^{2} = 0 --- (i)

First part:
6x^{2} - xy - y^{2} = 0

or, 6x^{2} - (3 - 2)xy - y^{2} = 0

or, 6x^{2} - 3xy + 2xy - y^{2} = 0

or, 3x(2x - y) + y(2x - y) = 0

or, (2x - y)(3x + y) = 0

Either, 2x - y = 0

OR, 3x + y = 0

So, the separate equations of the pair of lines represented by (i) are 2x - y = 0 and 3x + y = 0.

Second part:

Comparing equation (i) with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 6, h = -$\frac12$, b = -1

Let θ be the angle between lines represented by equation (i), we have,
tanθ = $\frac{\pm 2\sqrt{h^2\text{ - ab}}}{\text{a + b}}$
or, tanθ = $\frac{\pm 2\sqrt{(-\frac12)^2\text{ - (-6)}}}{\text{6 - 1}}$

or, tanθ = $\frac{\pm 2\sqrt{\text{1 + 24}}}{2 \times 5}$

or, tanθ = $\frac{\pm \sqrt{25}}{5}$

or, tanθ = ±1

Taking positive,

or, tanθ = tan45°

so, θ = 45°

Taking negative,

or, tanθ = -tan45°

or, tanθ = tan(180° - 45°)

so, θ = 135°

Hence, angle between a pair of lines represented by given equation is 45° or 135°.

The angle between a pair of straight lines is represented by the equation x^{2}
+ xy - ky^{2} = 0 is 45°. Find the value of `k`.

Here,

Given equation: x^{2}
+ xy - ky^{2} = 0 --- (i)

Comparing it with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 1, h = $\frac 12$, b = -k

Since 45° is the angle between lines represented by equation (i), we have,
tanθ = $\frac{\pm 2\sqrt{h^2\text{ - ab}}}{\text{a + b}}$
or, tan45° = $\frac{\pm 2\sqrt{(\frac12)^2\text{ - (-k)}}}{\text{1 - k}}$

or, 1 = $\frac{\pm 2\sqrt{\text{1 + 4k}}}{\text{2(1 - k)}}$

or, 1(1 - k) = ±$\sqrt{\text{1 + 4k}}$

Squaring on both sides, we get,

or, 1 - 2k + k^{2} = 1 + 4k

or, k^{2} - 6k = 0

or, k(k - 6) = 0

Either, k = 0

OR, k = 6

Hence, the value of `k` is 0 or 6.

Find the equations of the pair of lines represented by the equation 2x^{2} + 3xy + y^{2} = 0 and find the angle between them.

Given equation: 2x^{2} + 3xy + y^{2} = 0 --- (i)

First part:
2x^{2} + 3xy + y^{2} = 0

or, 2x^{2} + (2 + 1)xy + y^{2} = 0

or, 2x^{2} + 2xy + xy + y^{2} = 0

or, 2x(x + y) + y(x + y) = 0

or, (x + y)(2x + y) = 0

Either, 2x + y = 0

OR, x + y = 0

So, the separate equations of the pair of lines represented by (i) are 2x + y = 0 and x + y = 0.

Second part:

Comparing equation (i) with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 2, h = $\frac32$, b = 1

Let θ be the angle between lines represented by equation (i), we have,
tanθ = $\frac{\pm 2\sqrt{h^2\text{ - ab}}}{\text{a + b}}$
or, tanθ = $\frac{\pm 2\sqrt{(\frac32)^2\text{ - 2}}}{\text{2 + 1}}$

or, tanθ = $\frac{\pm 2\sqrt{\text{9 - 8}}}{2 \times 3}$

or, tanθ = ±$\frac13$

so, θ = tan^{-1}$(\pm\frac13)$

Hence, angle between a pair of lines represented by given equation is tan^{-1}$(\pm\frac13)$.

If the angle between the lines represented by 2x^{2} + kxy + 3y^{2} = 0 is 45°, find the value of `k`.

^{2}+ kxy + 3y

^{2}= 0 --- (i)

Comparing it with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 2, h = $\frac k2$, b = 3

Since 45° is the angle between lines represented by equation (i), we have,
tanθ = $\frac{\pm 2\sqrt{h^2\text{ - ab}}}{\text{a + b}}$
or, tan45° = $\frac{\pm 2\sqrt{(\frac k2)^2\text{ - 6}}}{\text{2 + 3}}$
or, 1 = $\frac{\pm 2\sqrt{k^2\text{ - 24}}}{2 \times 5}$
or, 5 = ±$\sqrt{k^2\text{ - 24}}$

Squaring on both sides, we get,

or, 25 = k^{2} - 24

or, 49 = k^{2}

so, k = ±7
Hence, the value of `k` is ±7.

If the straight lines represented by 5x^{2} - 8xy + py^{2} = 0
are perpendicular to each other, then find the value of `p`. Also find the equations of straight lines represented by 5x^{2} - 8xy + (p + 8)y^{2} = 0.

Given equation: 5x

^{2}- 8xy + py

^{2}= 0 --- (i)

Comparing it with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 5, h = -4, b = `p`

Since the lines represented by equation (i) are perpendicular,
a + b = 0
or, 5 + `p` = 0

so, `p` = 5 --- (ii)

Second Part:

Given equation: 5x^{2} - 8xy + (p + 8)y^{2} = 0

Using (ii),
5x^{2} - 8xy + (-5 + 8)y^{2} = 0 (from ii)
or, 5x^{2} - 8xy + 3y^{2} = 0

or, 5x^{2} - (5 + 3)xy + 3y^{2} = 0

or, 5x^{2} - 5xy - 3xy + 3y^{2} = 0

or, 5x(x - y) - 3y(x - y) = 0

or, (x - y)(5x - 3y) = 0

Either, x - y = 0

OR, 5x - 3y = 0

Hence, the separate equations of the pair of lines represented by the given equation are x - y = 0 and 5x - 3y = 0.

Find the equation of lines which pass through the point (1, 2) and
perpendicular to the lines represented by x^{2} - 5xy + 4y^{2}
= 0.

_{1}= m

_{1}(x -

_{1})

or, y - 2 = m

_{1}(x - 1) --- (i)

Now, for separate equations,
x^{2} - 5xy + 4y^{2}
= 0
or, x^{2} - (4 + 1)xy + 4y^{2}
= 0

or, x^{2} - 4xy - xy + 4y^{2} = 0

or, x(x - 4y) - y(x - 4y) = 0

or, (x - 4y)(x - y) = 0

Either, x - y = 0 --- (ii)

OR, x - 4y = 0 --- (iii)

From (ii),

slope (m_{2}) = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = 1

Since (i) and (ii) are perpendicular,
m_{1} × m_{2} = -1

or, m_{1} = -1

So, from (i),
y - 2 = -1(x - 1)

or, y - 2 = -x + 1
so, x + y - 3 = 0 --- (A)

Again, from (iii),

slope (m_{3}) = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = $\frac 14$

Since (i) and (iii) are also perpendicular,
m_{1} × m_{3} = -1
or, m_{1} = -4

Again, from (i),
y - 2 = -4(x - 1)

or, y - 2 = -4x + 4

so, 4x + y - 6 = 0 --- (B)

Finally, multiplying (A) and (B),
(x + y - 3)(4x + y - 6) = 0
or, 4x^{2} + xy - 6x + 4xy + y^{2} - 6y - 12x - 3y + 18 = 0

or, 4x^{2} + 5xy - 18x - 9y + 18 + y^{2} = 0

so, 4x^{2} + 5xy + y^{2} - 18x - 9y + 18 = 0

Hence, 4x^{2} + 5xy + y^{2} - 18x - 9y + 18 = 0 is the required equation.

Find the single equation of a pair of straight lines passing through the
origin and perpendicular to the lines represented by the equation 2x^{2}
- 7xy + 5y^{2} = 0.

_{1}= m

_{1}(x -

_{1})

or, y - 0 = m

_{1}(x - 0)

or, y = m

_{1}x --- (i)

Now, for separate equations,
2x^{2} - 7xy + 5y^{2} = 0
or, 2x^{2} - (5 + 2)xy + 5y^{2}
= 0

or, 2x^{2} - 5xy - 2xy + 5y^{2} = 0

or, x(2x - 5y) - y(2x - 5y) = 0

or, (2x - 5y)(x - y) = 0

Either, 2x - 5y= 0 --- (ii)

OR, x - y = 0 --- (iii)

From (ii),

slope (m_{2}) = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = $\frac 25$

Since (i) and (ii) are perpendicular,
m_{1} × m_{2} = -1

or, m_{1} = -$\frac 52$

So, from (i), y = -$\frac 52$x so, 5x + 2y = 0 --- (A)

Again, from (iii),

slope (m_{3}) = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = 1

Since (i) and (iii) are also perpendicular,
m_{1} × m_{3} = -1

or, m_{1} = -1

Again, from (i),
y = -1x

so, x + y = 0 --- (B)

Finally, multiplying (A) and (B),
(5x + 2y)(x + y) = 0
or, 5x^{2} + 5xy + 2xy + 2y^{2} = 0

so, 5x^{2} + 7xy + 2y^{2} = 0

Hence, 5x^{2} + 7xy + 2y^{2} = 0 is the required equation.

Find the single equation of a pair of straight lines passing through the
origin and perpendicular to the lines represented by the equation 2x^{2} - 3xy - 5y^{2} = 0.

_{1}= m

_{1}(x -

_{1})

or, y - 0 = m

_{1}(x - 0) or, y = m

_{1}x --- (i)

Now, for separate equations,
2x^{2} - 3xy - 5y^{2} = 0
or, 2x^{2} - (5 - 2)xy - 5y^{2}
= 0

or, 2x^{2} - 5xy + 2xy - 5y^{2} = 0

or, x(2x - 5y) + y(2x - 5y) = 0

or, (2x - 5y)(x + y) = 0

Either, 2x - 5y = 0 --- (ii)

OR, x + y = 0 --- (iii)

From (ii),

slope (m_{2}) = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = $\frac 25$

Since (i) and (ii) are perpendicular,
m_{1} × m_{2} = -1

or, m_{1} = -$\frac 52$

So, from (i), y = -$\frac 52$x so, 5x + 2y = 0 --- (A)

Again, from (iii),

slope (m_{3}) = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = -1

Since (i) and (iii) are also perpendicular,
m_{1} × m_{3} = -1
or, m_{1} = 1

Again, from (i), y = x so, x - y = 0 --- (B)

Finally, multiplying (A) and (B),
(5x + 2y)(x - y) = 0
or, 5x^{2} - 5xy + 2xy - 2y^{2} = 0

so, 5x^{2} - 3xy - 2y^{2} = 0

Hence, 5x^{2} - 3xy - 2y^{2} = 0 is the required equation.

If the two straight line represented by an equation 3x^{2} + 8xy +
my^{2} = 0 are perpendicular to each other, find the separate equation
of two lines.

^{2}+ 8xy + my

^{2}= 0 --- (i)

Comparing it with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 3, h = 4, b = `m`

Since lines represented by equation (i) are perpendicular,
a + b = 0

or, 3 + `m` = 0

so, `m` = -3 --- (ii)

Now, for separate equations,
3x^{2} + 8xy + my^{2} = 0
or, 3x^{2} + 8xy - 3y^{2} = 0 (from i)

or, 3x^{2} + (9 - 1)xy - 3y^{2} = 0

or, 3x^{2} + 9xy - xy - 3y^{2} = 0

or, 3x(x + 3y) - y(x + 3y) = 0

or, (3x - y)(x + 3y) = 0

Either, 3x - y = 0

OR, x + 3y = 0

Hence, the separate equations of the pair of lines represented by (i) are 3x - y = 0 and x + 3y = 0.

Find the single equation of the pair of straight lines passing through the
origin and perpendicular to the pair of lines represented by an equation
2x^{2} - 3xy + y^{2} = 0.

_{1}= m

_{1}(x -

_{1}) or, y - 0 = m

_{1}(x - 0) or, y = m

_{1}x --- (i)

Now, for separate equations,
2x^{2} - 3xy + y^{2} = 0
or, 2x^{2} - (2 + 1)xy + y^{2}
= 0

or, 2x^{2} - 2xy - xy + y^{2} = 0

or, 2x(x - y) - y(x - y) = 0

or, (2x - y)(x - y) = 0

Either, 2x - y = 0 --- (ii)

OR, x - y = 0 --- (iii)

From (ii),

slope (m_{2}) = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = 2

Since (i) and (ii) are perpendicular,
m_{1} × m_{2} = -1

or, m_{1} = -$\frac 12$

So, from (i),
y = -$\frac 12$x

so, x + 2y = 0 --- (A)

Again, from (iii),

slope (m_{3}) = -$\frac{\text{Coefficient of x}}{\text{Coefficient of y}}$ = 1

Since (i) and (iii) are also perpendicular,
m_{1} × m_{3} = -1

or, m_{1} = -1

Again, from (i), y = -x so, x + y = 0 --- (B)

Finally, multiplying (A) and (B),
(x + 2y)(x + y) = 0
or, x^{2} + xy + 2xy + 2y^{2} = 0

So, x^{2} + 3xy + 2y^{2} = 0

Hence, x^{2} + 3xy + 2y^{2} = 0 is the required equation.

Find the acute angle between the pair of lines given by 3x^{2} + 7xy +
2y^{2} = 0.

^{2}+ 7xy + 2y

^{2}= 0 --- (i)

Comparing it with ax^{2} + 2hxy + by^{2} = 0, we get,

a = 3, h = $\frac 72$, b = 2

Let, θ be the acute angle between lines represented by equation (i), we have,
tanθ = +$\frac{2\sqrt{h^2\text{ - ab}}}{\text{a + b}}$
or, tanθ = +$\frac{2\sqrt{\text{49 - 24}}}{\text{2(3 + 2)}}$

or, tanθ = +$\frac 55$

or, tanθ = +1

or, tanθ = tan45°

so, θ = 45°

Hence, the acute angle between a pair of lines represented by given equation is 45°.